Hard-Rod Behavior in Dense Mesophases of Semiflexible and Rigid Charged Viruses - Eric Grelet (Physical Review X, 2014)
We report on the phase behavior of a model system of colloidal rodlike particles, namely, the filamentous fd viruses, in the dense liquid crystalline states. After determining the phase boundaries as a function of the added salt, we propose a renormalization of the phase diagram accounting for the screened electrostatic repulsions between the particles through an effective hard-rod diameter. Including explicitly counterion condensation, we show that our heuristic model captures the main feature of the nematic-to-smectic phase transition of long hard rods, i.e., its universal packing fraction. The importance of rod flexibility on the relative stability of the different concentrated mesophases is also demonstrated, evidencing, in particular, the existence of a smectic-B phase in between the smectic-A and the columnar phases.